MMS : mobile monitoring system using electrical capacitance tomography (ECT) - Abdul Rahim, Ruzairi; Chan, Kok Seong (Faculty of Electrical Engineering, 2008)
Electrical capacitance tomography system is useful for obtain information about the spatial distribution of a mixture of dielectric materials inside a vessel. This research is aimed to obtain real-time monitoring on the composition for liquid mixture in conveying pipeline. ECT is a non-invasive, non-intrusive and non-destructive technique that can measure the flow level inside a pipeline. In order to increase the image resolution and result accurately of current tomography research, a study on 16 electrodes sensor ECT system has been developed. The developed system has the mobility to be assembled and moved from a pipeline to another. The intelligent on-board mobility sensor technique is never been applied on ECT system, it is a new technique and investigation of ECT system. The system however can be assembled in different diameter sizes of pipeline. and numbers of electrodes sensor can be reduced due to different size of pipeline without redesign the electrodes sensor. In order to reduce the cost of an ECT system, Universal Serial Bus technology (USB) has been used as the data transferring method. The final target of a tomography system is to control process and output of the pipeline and therefore a very high speed measurement and data transferring method is required to monitor the materials flow inside the pipeline. In this case, a high speed data processing rate data acquisition system and a high speed data reconstruction and image display system have been developed. As the result, a microcontroller that support full-speed USB data transfer rate has been designed as the centralization control unit. The reconstruction image process in the PC was written using programming platform Visual Basic 6.0. The information obtained in the PC can be reconstructed using linear back projection algorithm. In order to improve data result, iterative algorithm has been implemented in this system in order to obtain a precise image of the flow in the pipeline.